Pengaruh Perencanaan Sumber Daya Manusia Terhadap Kinerja Usaha Ruang Kuphi - Harmen, Hilma; Ardiansyah, Albert Tunggul; Islami, Dian Putri; Ginting, Nabila Al Zahra; Situmorang, Oktaviane; Gurusinga, Radhitya Dava; Tampubolon, Shella Anjelika Br; Otovia, Tesya Lola; Tarigan, Yehezkiel Moris (Benefit: Journal of Bussiness, Economics, and Finance, 2025)
Human Resources (HR) planning has an important role in improving employee performance and business sustainability. This research analyzes the HR planning strategy at Ruang Kuphi using qualitative methods through literature studies and interviews with business owners. The research results show that recruitment strategies according to needs, experience-based training, and regular briefings help increase employee work effectiveness. Apart from that, an incentive system in the form of bonuses has been proven to increase motivation and productivity. The use of technology in recruitment and performance evaluation also supports more efficient HR management, while the reward and punishment system builds a disciplined and responsible work culture. To increase the effectiveness of HR planning, it is recommended that Ruang Kuphi further optimize technology, strengthen training programs and improve internal communication to create a harmonious and competitive work environment. With the right strategy, Ruang Kuphi can continue to grow and compete in an increasingly dynamic industry.